The Effectiveness Of Mathematics Learning Outcomes Through Smart Pocket Card Media (Picture Card And Number Card) In The ABA 15 Kindergarten - Rahayu, Yuyun Tri; Meilani, Sri Martini; Hapidin, Hapidin (Universitas Negeri Semarang, 2019)
This study aims to streamline mathematics learning outcomes through smart pocket card (picture cards and number cards) so that group B students can students in identifying and exploring mathematical abilities with further drawings that can be arranged into more complex material operations. This study uses a mix of methods with research and development methods (Research and Development) The product developed in this study is a model of early childhood mathematics learning through smart pocket card learning media (picture cards and number cards). As explained above, this research uses a mix methods approach with three main methods including descriptive, evaluative, and experimental methods. Descriptive method is used to collect data about the condition of products that have been compared for products to be developed, the condition of the users, students and teachers, as well as inhibiting and supporting factors for the creation of products to be created. The results found that the first effectiveness test was conducted at the Ikal East Jakarta Kindergarten, while the number of children used as a small group test sample was 8 children. From the paired test results in East Jakarta Ikal Kindergarten obtained t count 24.777 and t table 0.70639 so there is a significant difference or HO is rejected then H1 is accepted. So it can be concluded that there is a difference between children's mathematics learning outcomes before and after the smart pocket card learning media is given (picture cards and number cards). Large group test at Pertiwi Karangsoka Kindergarten, as for the number of children used as a large group trial of 20 children. From the t test results obtained t count 23.214 and t table 0.68695 or t count> t table then there is a significant difference or HO is rejected, because HO is rejected then H1 is accepted. So it can be concluded that there are differences between children's mathematics learning outcomes before and after being given the smart pocket card learning media (picture cards and number cards). The last media effectiveness test was conducted at Aba 15 Teluk Kindergarten. In this effectiveness test the researcher used a sample of 40 children, obtained t count 24.137 and t table 0, 68067 or t count> from t table, so there is a significant difference or Ho is rejected. Because Ho is rejected and H1 is accepted, it can be concluded that there are differences between children's mathematics learning outcomes before and after being given the smart pocket card learning media (picture cards and number cards). From the results of the effectiveness test at the three schools above it proves that the learning media of smart poceket cards (picture cards and number cards) developed by this researcher can significantly improve the learning outcomes of early childhood mathematics in kindergarten group B Aba 15 Teluk, therefore it can it was concluded that the process carried out in the development of the model as well as the results obtained from the application of the smart pocket card learning media (picture cards and number cards) met the criteria of a good learning media that had validity, was practical, and was effectively used as an alternative learning media for improve children's learning outcomes in mathematics. Keywords: mathematics learning outcomes, smart pocket cards, picture cards, number cards.